Translational Strategies Used In The Host Movie Manuscript And Its Subtitle - Handika, Reni Nur; , Dr. Dwi Haryanti, M.Hum; , Drs. Sigit Haryanto, M.Hum (2014)
The objectives of the study are to identify the kinds of strategies used in The Host movie and to know the dominant strategy used in The Host movie manuscript and its subtitle. This research used descriptive-qualitative research. Documentation is method to collect the data, there are 5 steps to collect the data, namely: reading the script of The Host movie manuscript, underlining the strategies used finds in The Host movie manuscript, retyping the data taken from The Host movie manuscript, colecting data, and coding the data that include strategies used in The Host movie manuscript, and its subtitle. The result of this study show that they are five strategies used in The Host Movie Manuscript and Its Subtitle, They are five strategies used in The Host Movie Manuscript and Its Subtitle, first is addition (59 or 12.88%), that consists of addition of word (36 or 7.86 %), addition of phrase (3 or 0.66%), addition of clause (3 or 0.66%), and addition of sentence (17 or 3.71 %). Second is deletion (150 or 32.75%) that consist of deletion of word (70 or 12.28%), deletion of phrase (22 or 4.80 %), deletion of clause (25 or 5.49%), and deletion of sentence (33 or 7.21%). Third strategy is adoption (14 or 3.06%). Fourth adaptation (5 or 1.09%). The last type of strategy is translation shift (230 or 50,22%), that consist of level shift (122 or 26.64%), structural shift (65 data or 14.19%), class shift (18 0r 3.93%) and intra-system shift (25 or 5.49%), Based on the result it means that the dominant strategy used by the translator is level shift.